Penggunaan Model Picture And Picture Dalam Pembelajaran Menulis Puisi Pada Siswa Kelas X SMK Negeri 3 Karawang - Pebriyani, Fira; Mujtaba, Sahlan; Hartati, Dian (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to describe the use of the picture and picture model in learning to write poetry for class X students at SMK Negeri 3 Karawang. Based on the research objectives, the researcher hypothesizes that using the Picture and Picture Model is better than not using the Picture and Picture Model. The population in this study were all students of SMK Negeri 3 Karawang. Sampling was carried out using a purposive sampling technique with class X MP 1 as the control class and X MP 3 as the experimental class. Both sample classes have the same number, namely 36 students. The method used in this research is a quasi-experimental design with a pretest-posttest control group design, while for quantitative data analysis using software version 26.0 for Windows. Based on the results of the Normality test calculations, abnormal significance data is produced. Next, the Mann-Whitney Test was carried out. Based on the Test Statistics output, it is known that the Asymp Sig value. (2-tailed) of 0.000 < 0.05. From the formulation of this hypothesis, it can be concluded that H0 is rejected and H1 is accepted. There is a significant difference in the ability to write poetry between the experimental class and the control class. It can be concluded that the final ability to write poetry for students who use the Picture and Picture Model is better than using the conventional model seen from the assessment of the physical elements and inner elements that make up poetry